'Who knows best' - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The 'we know best' approach has predominated in deciding priorities and planning projects in rural areas. Unfortunately it has been the outside experts and not the local people whose opinions have predominated. At a recent meeting' to review and...